Tying the Knot: A Holistic Approach to the Enhancement of Religious Minority Rights and Freedom of Religion - Ferrari, Silvio (Religions, 2021)
The debate on religious minority rights has long been stranded in the shallows of a sterile juxtaposition between the politics of sameness and the politics of difference [...]